2021
DOI: 10.1016/j.biortech.2021.124815
|View full text |Cite
|
Sign up to set email alerts
|

Marine bacteria associated with the green seaweed Ulva sp. for the production of polyhydroxyalkanoates

Abstract: The biosynthesis of polyhydroxyalkanoate (PHA) biopolymers from certain marine microbes, associated with green macroalgae Ulva sp., has attracted significant attention. The Ulva sp. is abundant biomass in numerous locations around the world and could be easily cultivated by marine farming. The variety of sugars found in Ulva sp. homogenate could be used as a carbon source for microbial growth and PHA production. In this work, we isolated and explored a series of bacterial strains that function as potential pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The lignin is a major component of vascular plant tissue (Pollegioni et al, 2015), it also found in seagrasses (Opsahl and Benner, 1993;Klap et al, 2000;Pfeifer and Classen, 2020). The genus Cobetia has been isolated from green macroalgae Ulva sp., with some other species assimilating various carbon sources to produce polyhydroxyalkanoate (PHA; Gnaim et al, 2021). Previous studies of the eelgrass microbiome have focused on randomly selected leaf blades, regardless of leaf age (Ettinger et al, 2017;Fahimipour et al, 2017;Iqbal et al, 2021).…”
Section: Community Composition Of Phyllosphere and Rooting Zone (The ...mentioning
confidence: 99%
“…The lignin is a major component of vascular plant tissue (Pollegioni et al, 2015), it also found in seagrasses (Opsahl and Benner, 1993;Klap et al, 2000;Pfeifer and Classen, 2020). The genus Cobetia has been isolated from green macroalgae Ulva sp., with some other species assimilating various carbon sources to produce polyhydroxyalkanoate (PHA; Gnaim et al, 2021). Previous studies of the eelgrass microbiome have focused on randomly selected leaf blades, regardless of leaf age (Ettinger et al, 2017;Fahimipour et al, 2017;Iqbal et al, 2021).…”
Section: Community Composition Of Phyllosphere and Rooting Zone (The ...mentioning
confidence: 99%
“…and Laminaria japonica obtained after acid treatments have also been considered for the production of PHAs [38,39]. For the green seaweed Ulva sp., several treatments to release monosaccharides for subsequent production of PHAs have been considered, including acid hydrolysis [40,41], subcritical water extraction [42], and hydrothermal extraction of cellulose and starch [34]. Most of these pretreatments are challenging to achieve at large scale, are not environmentally friendly and create additional costs for an already non-cost-competitive process.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that the eutrophic environment during the bloom was not suitable for the growth of the oligotrophic SAR11 clade ( 35 ). Some phages whose potential hosts were associated with degradation of algae-derived organic matter were found, such as the Sulfitobacter ( 36 ), Cycloclasticus ( 37 ), Vibrio ( 10 , 38 , 39 ), Bacilli ( 40 ), and Roseobacter ( 41 ) ( Tables S3 and S4 ). These phages had similar temporal distribution patterns to their hosts, or there was a time delay between the peak in relative abundances of the virus OTUs and the putative host OTUs.…”
Section: Discussionmentioning
confidence: 99%